If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -4 = -2x + -25 Reorder the terms: -4 + 5x = -2x + -25 Reorder the terms: -4 + 5x = -25 + -2x Solving -4 + 5x = -25 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -4 + 5x + 2x = -25 + -2x + 2x Combine like terms: 5x + 2x = 7x -4 + 7x = -25 + -2x + 2x Combine like terms: -2x + 2x = 0 -4 + 7x = -25 + 0 -4 + 7x = -25 Add '4' to each side of the equation. -4 + 4 + 7x = -25 + 4 Combine like terms: -4 + 4 = 0 0 + 7x = -25 + 4 7x = -25 + 4 Combine like terms: -25 + 4 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| -3x-17=-44 | | 8x-7=3x-17 | | x+(.4x*.5x*.145x)=19130 | | Y=-0.8t+40 | | 8x+14=4x+34 | | 113-303= | | 33(-5)= | | 6=-10d+2 | | 33x-5= | | 2x^2-4x+103=0 | | 2x^2-4x-103=0 | | 6-7d=-3D+2 | | 15-2x=0 | | -6x^2-2x-1=0 | | 8=-5x-3 | | -366+k=170 | | 17+4(3+q)-a= | | 3x-5(0.6x-1)=3 | | 4(3+9)+10a-41= | | M+-2=67 | | 6x-24=4x-2-6 | | 2(3-3x)=94 | | 6x+8+2x=4(5+x) | | 3f+47-2f=40 | | 2-(2x-1)+7x=10 | | 5x+22=100+3x | | 6x-3(0.2x+3)=2x | | 3(x+4)-2x=5 | | 56-2g=6g | | 16-3x=27 | | 6+x=-25 | | 8x-17=1x-17 |